The Role of Deployment Policies in Fostering Innovation for Clean Energy Technologies: Insights From the Solar Photovoltaic Industry. (July 2015) - Hoppmann, Joern
In recent years, governments in a large number of countries have introduced so-called deployment policies to foster the diffusion of clean energy technologies. While there is little doubt that these demand-side measures have been very effective in raising the share of clean electricity generation, currently, much less is known about how deployment policies affect—and are affected by—technological innovation beyond the mere diffusion of existing technologies. Against this backdrop, this dissertation abstract and commentary presents the dissertation work of Dr. Joern Hoppmann. Based on a discussion of deployment policies as a means for addressing pressing societal issues, the dissertation abstract describes four essays that provide a detailed account of the role that these policies play for technological learning in the solar photovoltaic (PV) industry. The theoretical background, methods, and main findings of each of the essays are briefly summarized. Building on this, this abstract discusses implications for managers and policy makers in terms of how to improve the design of deployment policies and navigate businesses in policy-induced markets.